Pendampingan Penggunaan Financial Technology Di Era Society 5.0 Di Desa Saribaye Kecamatan Lingsar Lobar - Nurabiah, Nurabiah; Pusparini, Herlina; Fitriyah, Nur; Bambang, Bambang; Mariadi, Yusli; Aprilian, Imam Yuardi; Setiawati, Rani; Santoso, Aprilia; Wulan, Putri Cahya (Jurnal Gema Ngabdi, 2024)
Saribaye Village is one of the villages in NTB that is of concern for financial literacy issues. One of the programs held by the NTB Province OJK is the "sobat sikapi" program. This service aims to increase understanding and good use of fintech for young people and MSMEs in Saribaye village and can be implemented in everyday life. To solve partner problems related to understanding and using digital financial applications in the form of payment systems on Gojek, OVO, Shopee, Bukalapak, Tokopedia, Tcash, Dana and Paytren, the implementation of this service consists of two stages, including 1) First Stage, providing knowledge and information about digital finance in the form of payment systems on Gojek, OVO, Shopee, Bukalapak, Tokopedia, Tcash, Dana and also Paytren to make them understand more about the benefits of using fintech. 2) Second stage, offline and online consultation assistance. If there are young people and MSME players who still don't understand what digital finance is and its use, they can ask at any time via the service team's WhatsApp or via email to each service team. In this training, the methods are lecture, practice, and discussion. This mentoring was attended by 26 participants. After conducting the survey, the results showed that the level of financial literacy in the form of respondents' use of fintech was good. This was proven by 40.9% of the average respondents' answers indicating good financial literacy, 38.3% showed quite good results and 20.9% showed poor results.  Keywords: mentoring; financial literacy; digital finance